2013
DOI: 10.1021/jp400842r
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of the Novel Ag3VO4/AgBr/Ag Plasmonic Photocatalyst with Enhanced Photocatalytic Activity and Stability

Abstract: A novel ternary plasmonic Ag 3 VO 4 /AgBr/Ag hybrid photocatalyst was successfully fabricated via an in situ anion-exchange reaction between Ag 3 VO 4 and KBr, followed by light reduction. The obtained samples were characterized by X-ray diffraction, scanning electron microscopy, energydispersive X-ray spectroscopy, UV−visible diffuse-reflectance spectroscopy (UV−vis DRS), and X-ray photoelectron spectroscopy. The photocatalytic activities of obtained photocatalysts were measured by the degradation of Rhodamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(85 citation statements)
references
References 48 publications
3
82
0
Order By: Relevance
“…Therefore, a relative high concentration electrons on the surface of CNTs is formed, which can be trapped by O 2 and H 2 O to from H 2 O 2 (Eqs. (3)- (5)) [37,43,44]. These RSs, such as h + , e − and H 2 O 2 , could attack the E. coli, disrupt cell membrane and result in ultimate cell death (Eq.…”
Section: Photocatalytic Bacterial Inactivation Mechanismmentioning
confidence: 99%
“…Therefore, a relative high concentration electrons on the surface of CNTs is formed, which can be trapped by O 2 and H 2 O to from H 2 O 2 (Eqs. (3)- (5)) [37,43,44]. These RSs, such as h + , e − and H 2 O 2 , could attack the E. coli, disrupt cell membrane and result in ultimate cell death (Eq.…”
Section: Photocatalytic Bacterial Inactivation Mechanismmentioning
confidence: 99%
“…Strong evidence reveals that the plasmonic effect not only plays a quite positive role in enhancing the rate of photocatalytic reactions on nearby semiconductors, but also possibly interacts with the entire solar spectrum when appropriate resonant wavelength and SPR intensity are obtained in a well-designed plasmonic nanostructure [1]. It has been reported that metal/semiconductor composite materials, such as Au/TiO 2 or Ag/N-TiO 2 composites [1], Ag@AgCl cubic cages with well-defined hollow interiors [4], hybrid nanoparticles with cubic AgCl cores and Ag nanograin coating [5], Ag nanoparticles/AgX (X = Cl, Br, and I) [6], Ag 3 VO 4 /AgBr/Ag ternary hybrids [7], showed significantly higher photocatalytic degradation rates than their single counterparts in a number of reactions [1]. Although much improved photocatalytic activities could be achieved over these metal/semiconductor composite materials, they still lacked the aforementioned optimized architecture.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of O 2 adsorbed on surface were reduced to O 2 -by e -and then converted to active hydroxyl radicals ( ), a strong oxidant, which persistently attacked the MO molecules until they are degraded completely (22,25). Meanwhile, the surface h + are apt to undergo charge transfer with adsorbed water molecules or surface-bound hydroxide species to generate active (26).…”
Section: Photocatalytic Mechanism Discussionmentioning
confidence: 99%